Human–elephant conflict and land cover change in Sri Lanka. (June 2022) - Rathnayake, Chithrangani W.M.; Jones, Simon; Soto-Berelov, Mariela; Wallace, Luke
Abstract: Human–elephant conflict (HEC) is a key environmental issue in number of Asian countries, including Sri Lanka. Incidents of HEC have significantly increased in Sri Lanka between 1991 and 2018, with 1734 human deaths reported in this period (281% increase), 4837 elephant deaths (1172% increase), 1053 human injuries (140% increase) and more than 23, 000 property damage reports (1406% increase). In this study we present a Sri Lanka wide analysis to explore the role of land use and land cover change (LULCC) in relation to HEC, using official government data and a land cover change dataset (1993–2018) recently developed by the authors using satellite imagery from the Landsat archive. We investigated rates of HEC over time and compared these to rates of LULCC over the same period. We also present spatial analytics of HEC and LULCC, as well as determining hotspots of HEC and LULCC using a kernel density estimator. Annual HEC incidents were found to broadly increase in line with land use change events (r = 0.43, p < 0.05). Human deaths, elephant deaths, human injuries and property damage hotspots show distinct spatial patterns: human deaths and injuries being more concentrated in the North West, Polonnaruwa and Ampara, wildlife regions; while elephant deaths are spread throughout the HEC region and property damage is high in the Central, Polonnaruwa Anuradhapura, North West, and Southern wildlife regions. We found a strong negative correlation between HEC location and distance to LULCC events. In total, 98% HEC occurred within 1 km of an area that experienced recent LULCC Since 2017, the primary HEC hotspots have shifted to the south and east of the country in concert with LULCC. These countrywide perspectives could help inform HEC mitigation strategies in Sri Lanka and other countries facing similar human-wildlife challenges. Highlights: We map the incidences of human-elephant (elephas maximus) conflict in Sri Lanka. We explore trends and patters of human elephant conflict in Sri Lanka. We discover the association between land use and cover change and human elephant conflict. Human death, elephant death, human injury, and property damage incidents and their spatial proximity to land cover change. Temporal patterns of land cover change hotspots and human elephant conflict hotspots in Sri Lanka.